Typical Males and Unconventional Females: Songs and Singing Behaviors of a Tropical, Duetting Oriole in the Breeding and Non-Breeding Season - Odom, Karan J.; Omland, Kevin E.; McCaffrey, David R.; Monroe, Michelle K.; Christhilf, Jennifer L.; Roberts, Natalie S.; Logue, David M. (Frontiers in Ecology and Evolution, 2016)
Recent research emphasizes that female song is evolutionarily important, yet there are still few species for which we have quantified the similarities and differences between male and female song. Comparing song rates and the structure of female and male song is an important first step to forming hypotheses about functional and evolutionary differences that may exist between females and males, especially in year-round territorial species that may use their songs for breeding and non-breeding activities. We compared female and male singing rates and song structure in a tropical New World oriole, the Venezuelan troupial (Icterus icterus) during both the breeding and non-breeding season and between the dawn and day. Males sang solos at particularly high rates during the breeding season before dawn. Females, however, sang at consistent rates year-round, primarily during the day. Females answered 75% of male day songs, producing duets, whereas males overlapped only 42% of female songs. Duets were common year-round, but occurred more often during the non-breeding season. Structurally, female songs were higher pitched and shorter than male songs. We detected no sex differences in the number or order of syllables, however, interestingly, answers were shorter than duet initiations and solos, and, during the breeding season, songs that initiated duets were characterized by higher syllable diversity than were answers or solos. The fact that males sing more during the breeding season supports the classical hypothesis that male song is a sexually selected trait. However, our findings that females sing solos and answer the majority of male songs to create duets year-round suggests that female song may have evolved to serve multiple functions not exclusively tied to breeding.